STATUS OF FISHERIES MANAGEMENT WITH AN ECOSYSTEM APPROACH IN THE DOMAIN FISH RESOURCES FOR TERUBUK (Tenualosa macrura) IN BENGKALIS REGENCY, RIAU PROVINCE - Rizki Adiwanarta; Adriman Adriman; Deni Efizon (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This study aims as follows: 1) To determine the status of ecosystem-based fisheries management or Ecosystems Approach of Fisheries Management (EAFM) in the domain of fish resources for terubuk fish in Bengkalis Regency, Riau Province. The method used in this research is survey, observation and interview methods. The results of this study indicate that the indicators for the Composition of Catched Species and ETP Species of Fish Resources are still in good status. Meanwhile, indicators that need to be prioritized for improvement in sustainable fisheries management in the future because it is already in a moderate to bad status are Raw CPUE and Fish Size Trends. The conclusion of this research shows that fisheries management for terubuk fisheries (Tenualosa macrura) is still in good condition with green flag modeling and a mean value of 2,7.